Effect of Histone Acetylation on N-Methyl-d-Aspartate 2B Receptor Subunits and Interleukin-1 Receptors in Association with Nociception-Related Somatosensory Cortex Dysfunction in a Mouse Model of Sepsis. Issue 6 (June 2016) - Imamura, Yukio; Yoshikawa, Nao; Murkami, Yuki; Mitani, Satoko; Matsumoto, Naoya; Matsumoto, Hisatake; Yamada, Tomoki; Yamakawa, Kazuma; Nakagawa, Junichiro; Ogura, Hiroshi; Shimazu, Takeshi; Jin, Takashi
Abstract : ABSTRACT: Whole-body inflammation (i.e., sepsis) often results in brain-related sensory dysfunction. We previously reported that interleukin (IL)-1 resulted in synaptic dysfunction of septic encephalopathy, but the underlying molecular mechanisms remain unknown, as do effective treatments. Using mice, we examined immunohistochemistry, co-immunoprecipitation, enzyme-linked immunosorbent assay, and behavior analyses, and investigated the role of the N-methyl-d -aspartate 2B subunit (NR2B) of NMDA receptor, IL-1 receptor, and histone acetylation in the pathophysiology underlying sensory dysfunction induced by lipopolysaccharide (LPS). Mice groups of sham-operated, LPS, LPS with an NR2B antagonist, or LPS with resveratrol (a histone acetylation activator) were analyzed. We found that LPS increased NR2B and interleukin-1 receptor (IL-1R) immunoreactivity. The expression of Iba1, a marker for microglia and/or macrophages, increased more significantly in the brain than in the spinal cord, implicating NR2B and IL-1R in brain inflammation. Immunoprecipitation with NR2B and IL-1R revealed related antibodies. Blood levels of IL-1β (i.e., the IL-1R ligand) increased, though not significantly, suggesting that inflammation peaked at 20 h. Behavioral assessments of central (CNS) and peripheral sensory (PNS) function indicated that LPS delayed CNS but not PNS escape latency. Finally, NR2B antagonist or resveratrol in the lateral ventricle antagonized the effects of LPS in the brain and improved animal survival. In summary, histone acetylation may control expression of NR2B and IL-1R, alleviating inflammation-induced sensory neuronal dysfunction caused by LPS.